Organizational Commitment in Public Sector Banks: A Comparative Study in India and Sri Lanka - Mangaleswaran, T.; Srinivasan, P.T. (My University, 2012)
This study compares organizational commitment of employees in Public Sector Banks in India and Sri Lanka. The investigation is based on a questionnaire survey of a sample of 449 employees drawn from 3 Public sector Banks in India and 281 employees from 2 public sector Banks in Sri Lanka. The key areas of analysis include the affective commitment, continuance commitment and normative commitment. The statistical analysis shows that there are significant differences between PSBs of two countries. The findings are discussed.